Trade Agreements in South Asia Towards a Successful Story in the Developing World - Franco-Bedoya, Sebastian (The World Bank, 2022)
This paper quantifies the trade creation effects of South Asia's trade agreements within the region and with the rest of the world. The paper uses an extensive database of bilateral trade covering the manufacturing, agriculture, and service sectors in 190 countries over 1990-2015. The estimates of various specifications of a structural gravity model, including domestic trade flows, capture the potential heterogeneous effects. The main finding is that these effects are in general stronger for trade agreements signed by South Asian countries and even stronger in the case of intraregional agreements. The effects of free trade agreements vary substantially among countries and sectors and between final and intermediate goods. The paper shows that the trade policy implemented in South Asia in the previous decades has been successful, but at the same time the results point toward the existence of clear missing opportunities for the region. The opportunities lay in (i) better backward integration with the rest of the world to improve efficiency and help strengthen exports, and (ii) further deepening of intraregional agreements to continue making progress in regional integration